2010
DOI: 10.4049/jimmunol.0903790
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase Activation Attenuates the TLR2-Mediated Macrophage Proinflammatory Cytokine Response toFrancisella tularensisLive Vaccine Strain

Abstract: We sought to clarify the role of the PI3‐kinase/Akt pathway in regulating early (< 9 h) proinflammatory responses in macrophages infected with Francisella tularensis Live Vaccine Strain (LVS). LVS‐induced TNF‐α and IL‐6 secretion was markedly increased in macrophages from wildtype C57BL/6 mice pre‐exposed to the PI3‐kinase inhibitor wortmannin compared with vehicle pre‐exposed macrophages; the levels of phosphorylated p38 MAPK and ERK1/2 were also enhanced and remained elevated for a longer period of time. LVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 96 publications
2
65
0
Order By: Relevance
“…However, another explanation is the potential autocrine action of M-CSF, or analogous growth factors, since in primary murine macrophages the p38 activation by CpGs, but not LPS, was suppressed by pretreatment with M-CSF which at the same time upregulated ERK phosphorylation [36]. In addition, it has been shown that the PI3K signalling suppresses TLR-induced p38 phosphorylation in innate immune cells including DCs [37] and macrophages [38]. Enhanced activity of PI3K in macrophages results in increased DUSP1 (a p38 specific phosphatase) expression, IL-10 production and, as a result, diminished p38 activation and lowered production of proinflammatory cytokines in response to pathogens [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, another explanation is the potential autocrine action of M-CSF, or analogous growth factors, since in primary murine macrophages the p38 activation by CpGs, but not LPS, was suppressed by pretreatment with M-CSF which at the same time upregulated ERK phosphorylation [36]. In addition, it has been shown that the PI3K signalling suppresses TLR-induced p38 phosphorylation in innate immune cells including DCs [37] and macrophages [38]. Enhanced activity of PI3K in macrophages results in increased DUSP1 (a p38 specific phosphatase) expression, IL-10 production and, as a result, diminished p38 activation and lowered production of proinflammatory cytokines in response to pathogens [39].…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 dimerization with TLR1 or TLR6 allows for recognition of both gram-positive and certain gram-negative bacteria (e.g., S. aureus, Streptococcus pneumoniae, Pseudomonas aeruginosa, Francisella tularensis) (4,6,7,9). C29 significantly inhibited heat-killed P. aeruginosa-induced and heat-killed S. aureus (HKSA)-induced IL-8 mRNA in HEK-TLR2 cells (Fig.…”
Section: C29 Blocks Tlr2 Bacterial Agonist-induced Proinflammatory Genementioning
confidence: 99%
“…TLR2 heterodimerizes with TLR6 or TLR1 to recognize diacyl lipopeptides or triacyl lipopeptides, respectively (2,3), present in gram-positive and gram-negative bacteria (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Some studies show that, in liver ischemic/reperfusion injury, PTEN can promote local macrophage activation, proinflammatory cytokine expression, and neutrophil accumulation through suppressing Akt/b-catenin-mediated NF-kB inhibition and promoting Foxo1-mediated NF-kB activation (27,28). Also, previous studies have shown that PI3K/Akt signaling could directly regulate MAPK activation (29) and GSK3 could directly crosstalk with NF-kB activation triggered by TLR agonists (30). Therefore, downregulating miR-3473b by IFN-g priming to suppress PI3K/Akt/ GSK3 signaling may also directly regulate TLR-triggered MAPK and NF-kB signaling to beef up macrophage activation.…”
Section: Figurementioning
confidence: 99%